Emotional labor among academics / Rosliza Md Zani, Anita Abu Hassan and Abd Rasyid Ramli - Md Zani, Rosliza; Abu Hassan, Anita; Ramli, Abd Rasyid (Universiti Teknologi MARA, Kedah, 2023)
Hochschild (1983) defines emotional labor as the management of emotions to create publicly observable representations of faces and bodies in exchange for payment. It is a situation in which an employee expresses organizationally desired emotions during interpersonal interactions at work (Robbins & Judge, 2019). Emotional labor involves managing emotions and emotional expressions to be in line with the expectations about appropriate emotional expressions that exist within a profession. It is said to be a stress factor for employees to regulate their feelings and expressions to achieve organizational goals. Emotional labor is frequently associated with caring acts, roles, and emotions in both paid and unpaid contexts. Emotional labor is considered a professional skill in the world of remunerated employment, which includes repressing personal feelings in favor of work-related or socially acceptable feelings. Emotional labor can be bought and sold and forms part of a worker's wages. Emotional work is seen as important in jobs that require workers to show emotions and generate emotions in others while performing work, such as teaching, social work, and health care (Hochschild, 2012; Mastracci, 2012, as cited in Newcomb, 2021).